2014
DOI: 10.18860/ling.v9i2.2546
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Model Project-Based Learning Untuk Meningkatkan Kemampuan Bahasa Inggris Siswa Ponpes Modern Di Malang Raya

Abstract: English is taught in Modern Islamic Boarding School  as one of  language competences must be mastered by the students  beside Arabic. The teachers find  difficulties to implement  learning models that make the students to be active  and  the students need others learning variation.  Research and Development (R &amp; D) design is used in this  research  that aim  to produce the development of <em>“Project Based-Learning Model”</em> plus VCD to improve the Students' English Ability of Modern Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The age of 6 to 12 years is a basic education period [17], according to Harvigust, the development of elementary school aged children includes [18], [19], [20]; a) Mastering physical skills used in games and physical activities, b) Building a healthy life, c) Learning to interact and work in groups, d) ) Learning to carry out social roles according to gender, e) Learning to read, write, and count so that you can participate in society, f) Acquiring a number of concepts needed to think effectively, g) Developing conscience, morals and values, and h) Achieving personal independence.…”
Section: Methodsmentioning
confidence: 99%
“…The age of 6 to 12 years is a basic education period [17], according to Harvigust, the development of elementary school aged children includes [18], [19], [20]; a) Mastering physical skills used in games and physical activities, b) Building a healthy life, c) Learning to interact and work in groups, d) ) Learning to carry out social roles according to gender, e) Learning to read, write, and count so that you can participate in society, f) Acquiring a number of concepts needed to think effectively, g) Developing conscience, morals and values, and h) Achieving personal independence.…”
Section: Methodsmentioning
confidence: 99%
“…More issues also arose. Firstly, teachers had limited knowledge and skills in teaching English with the use of appropriate methods, especially the ones that could promote active participation in such an Islamic setting (Suhartatik & Adi, 2014). This condition brought about ineffective lessons as pesantren students still showed a lack of English communication skills.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted centering around the issues of pesantren context. Suhartatik and Adi (2014) focused on developing a model of project-based learning by creating a video CD to improve pesantren students' English skills in Malang. Another study by Risdianto (2016) reported that the "army method", highly teacher-centered, was used in Pesantren in Surakarta, emphasizing rewards and punishment to improve students' language skills.…”
Section: Introductionmentioning
confidence: 99%
“…Wajdi (2017) yang mengembangkan pembelajaran berbasis proyek dalam pembelajaran drama menunjukkan hasil yang efektif: pembelajaran dapat diimplementasikan dengan muda dan nilai pembelajaran menunjukkan hasil yang memuaskan. Suhartatik & Adi (2014) menemukan bahwa pembelajaran berbasis proyek dapat meningkatkan keterampilan berbahasa Inggris dan membantu menyelesaikan masalah-masalah dalam belajar. Dalam hal motivasi belajar, Tamim dan Grant (2013) menemukan bahwa penggunaan pembelajaran berbasis proyek berhasis meningkatkan motivasi dan melibatkan secara aktif peserta didik dalam belajar.…”
unclassified